Need Analysis of English Material Adaptation for Accounting Study Program in Vocational High School - Maratus S., Alma; Wardhani, Ika Desy; Ismaili, Ismaili (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2023)
The researcher could analyse the student To investigate the students’ needs of practicing English through the need analysis perspective in the context of Vocational High School Investigating students and teacher perception in accounting program toward English targeted needs in one of Indonesian private Vocational High School, and As constructive inputs for curriculum designers to develop English materials for students’ accounting programs suited to their needs. Current study uses qualitative design and assessed student needs. Learn English in a vocational training in Indonesia. All necessary data were first collected by her web-based questionnaire and semi-structured interviews. The reason for using descriptive research is that qualitative approaches helps to better understand the research question than using either one (Creswell, 2014) We chose this study because we need to know deeply how the participants perceive the target's needs in the accounting space.